ANALISIS DAMPAK MOTIVASI KERJA, KOMPENSASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN CV MANDALA MULIA ABADI - Chandra, Amalia Ekasari Dewi; Asteria, Beta (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
This study intends to examine how the work environment, pay, and motivation of CV Mandala Mulia Abadi workers affect their performance. The population in this study were 50 employees of CV Mandala Mulia Abadi with information collection techniques using questionnaires and Likert scale measurements. The research instrument is in the form of a validity test and a reliability test. The analytical method of this research uses quantitative methods, multiple linear regression equations, t test, f test and the coefficient of determination (R2). The classical assumption test requirements that must be met are the normality test, linearity test, heteroscedasticity test, and multicollinearity test. The results of the study show (1) work motivation has no significant effect on employee performance, this can be seen from the results of the t-count test of 1.584 which is smaller than t-table 2.009 and the significance value is 0.120 > 0.05. (2) Compensation has a positive effect on employee performance, with a t-value of 4,563 > 2,009 and a sig value of 0,000 <0.05. (3) The work environment has no significant effect on employee performance, with a t-value of -0.675 <2.009 and a significance value of 0.503, which means greater than 0.05. (4) Work motivation, compensation, and work environment have a positive and simultaneous effect on employee performance with an F calculated value of 69.040 with a significance of 0.000.